PENGARUH JENIS PLASTIK SEBAGAI MEDIA PROSES BIOFILTRASI PADA PENURUNAN BOD LIMBAH CAIR TEMPE - Dafitra Rahmatullah; Hardoyo Hardoyo; Sulastri Sulastri (Lembaga Pengembangan Kinerja Dosen, 2025)
Tempeh is a processed product that is favored by most Indonesian people, by using cheap and easy-to-obtain soybean raw materials, making tempeh a promising processed product to be used as a business. Waste produced from the tempeh industry includes liquid waste. The purpose of the research was to utilize plastic media as a medium to reduce BOD in tempeh liquid waste. The research method used is a type of true experiment, the research uses Biofiltration tools with three plastic materials, PVC, PP, HDPE, and silica sand. The flow used is the Upflow (Batch) flow. The results of the study show that the three types of plastics, both PVC, PP, and HDPE, can be used as a medium in reducing BOD in tempeh liquid waste. This can be seen in the research until the 14th day, the use of PVC, PP, HDPE plastic materials can reduce BOD by as much as (PVC 72.8%, PP 75.5% and HDPE 76.9%).